2007
DOI: 10.1021/ja071073m
|View full text |Cite
|
Sign up to set email alerts
|

A Bell-Shaped Mn11Gd2 Single-Molecule Magnet

Abstract: The tridecanuclear heterovalent mixed-metal (Mn11Gd2) complex [MnIII 9MnII 2GdIII 2(O)8(OH)2(O2CR)17(NO3)2(H2O)] has been obtained from the reaction of the hexanuclear compound [Mn6O2(Piv)10(4-Me-py)2.5(PivH)1.5] with Gd(NO3)3·6H2O in CH3CN. The complex presents an unusual “bell”-shaped core with a high-spin ground state and is a new member of the high-nuclearity 3d-4f single-molecule magnets family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 292 publications
(74 citation statements)
references
References 18 publications
0
73
0
1
Order By: Relevance
“…Finding Recent research by us and others into mixed 3d/4f systems [9][10][11] offers various means to increase both spin and total anisotropy. En route we synthesised the Gd-containing isotropic member of a new series of cyclic CCs [Fe 10 Ln 10 (Me-tea) 10 (Me-teaH) 10 (2).…”
Section: Introductionmentioning
confidence: 99%
“…Finding Recent research by us and others into mixed 3d/4f systems [9][10][11] offers various means to increase both spin and total anisotropy. En route we synthesised the Gd-containing isotropic member of a new series of cyclic CCs [Fe 10 Ln 10 (Me-tea) 10 (Me-teaH) 10 (2).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The synthesis of molecules combining the magnetic moment and relatively strong exchange interactions of 3d transition metals (M) with the anisotropy naturally provided by lanthanide (Ln) ions is especially promising. Several molecular clusters of this type have been reported, such as {Mn 4 Ln 4 }, 10 {Mn 12 Gd}, 11 and {Cr 4 Dy 4 }, 12 with Ln = heavy Ln's, and {Mn 11 Ln 2 }, 13,14 with Ln = light rare earths. It was found that, in particular, Dy(III) ions are very useful for introducing anisotropy into these molecules, 15 thus confirming the possibility of achieving increased anisotropy in the lanthanide-transition-metal molecular combination.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Initially, much work concentrated on mixing 4f ions with Mn III . However, experience shows that relatively isotropic ions can also be used to help aggregate 3d-4f clusters in such a way as to produce new examples of SMMs often with enhanced SMM properties compared with the pure 3d analogues.…”
mentioning
confidence: 99%